Pros and Cons Comparison of Reporting on the Personal Data Protection Law in Tribunnews.com and Antaranews.com - Susanti, Defi; Fithri Ajhuri, Kayyis (Kalijaga Journal of Communication, 2023)
This article observes the framing contained in reports of Tribunnews.com and antarnews.com regarding the ratification of Law No. 27 of 2022 concerning Perlindungan Data Pribadi or Personal Data Protection (PDP) during September 2022. This article wants to know how the framing of the PDP Law works and what forms of the frame are carried out by Tribunnews.com and Antarnews.com. The emergence of the PDP Law cannot be separated from the context of problems related to leaks of people's data, which have been occurring in Indonesia. It is alleged that the PDP Law could solve the problem of leaking people's data. However, some other people think that the PDP Law does not guarantee that data security will be realized. Using a comparative qualitative descriptive approach, this research will focus on dissecting five news stories about the PDP Law published by Tribunnews.com and antarnews.com. The news used as a data source will be analyzed using Robert N. Entman's framing analysis model, which has four analysis tools: define problems, diagnose causes, make moral judgments, and make treatment recommendations. This research shows that there is a framing of the news about the PDP Law presented by Tribunnews.com and antarnews.com. Tribunnews.com frames the news about the PDP Law by highlighting its pros and cons. Meanwhile, antarnews.com only highlights the positive or pro side of the PDP Law. antarnews.com marginalizes opinions that view the PDP Law critically and tend to be against it.